1940
DOI: 10.1113/jphysiol.1940.sp003819
|View full text |Cite
|
Sign up to set email alerts
|

On the disappearance from the blood of intravenously injected insulin

Abstract: IT is not yet universally agreed which of the two hypotheses about the secretion of insulin by the pancreas is correct; whether insulin is periodically secreted in response to a rise in the blood-sugar concentration; or whether there is a continuous secretion at a constant rate, a more recent view put forward by Soskin, Allweiss & Cohn [1934].In either case, a certain amount of insulin is required daily by the body. Furthermore, when normal men or animals, or a diabetic patient, or an animal with experimentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1942
1942
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The effect of the kidneys on the removal of insulin from the blood has been appreciated since the observations of R ecordier and A n d r a c [111] and confirmed by many subsequent studies in various animal species [12,35,36,49,112]. Similar results were obtained in patients with severe renal disease and in renal transplant recipients.…”
Section: Metabolism O F Insulin By the Kidney Extractionsupporting
confidence: 75%
“…The effect of the kidneys on the removal of insulin from the blood has been appreciated since the observations of R ecordier and A n d r a c [111] and confirmed by many subsequent studies in various animal species [12,35,36,49,112]. Similar results were obtained in patients with severe renal disease and in renal transplant recipients.…”
Section: Metabolism O F Insulin By the Kidney Extractionsupporting
confidence: 75%
“…This result may be mainly due to the retardation of insulin because of its reduced de gradation in the kidney [7] and peripheral insulin resist ance [2,6], and it may be partially due to the hyperproinsulinemia in uremia which is biologically less active than insulin [20], that crossreacts with insulin antibodies used in the radioimmunoassay [21], From this study, it is suggested that there might be impairment of the initial insulin secretion without changes of insulin content in pancreatic islets in uremia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, insulin secretion is generally thought to be enhanced because of an elevated serum immunoreactive insulin (IRI) level during glucose tolerance test [1,[3][4][5]. However, as the kidney is a main organ for insulin metabolism and degradation [7,8], a high serum IRI level in chronic renal failure does not always mean increased secretion of insulin from the pancreas. In order to examine the true insulin secretion in chronic renal failure, we investigated the insulin release from perifused pancreatic islets of experimental uremic rats.…”
Section: Introductionmentioning
confidence: 99%
“…From these biological experiments it was reasonably concluded that after glucose loading insulin or an insulin derivative was excreted in the urine. Furthermore, Partos (1929) and Lawrence et al (1930) did not find blood sugar lowering substance in the urine of diabetics and fasted animals, while Recordier and Andrac (1935) and Goadby and Richardson (1940) demonstrated that the exclusion of the kidneys from the circulation in rabbits led to a persistence of insulin action in blood. It was inferred that the organs were partly responsible for the elimination of insulin from the blood, thereby implying the removal of insulin via urine.…”
Section: Introductionmentioning
confidence: 99%